Representasi Wacana Kalepasan sebagai Konsep Estetika dan Etika Spiritualitas Manusia dalam Kakawin Panca Dharma - Dwijayanthi, Ni Made Ari (Jurnal Penelitian Agama Hindu, 2025)
The Kakawin Panca Dharma (KPD), comprising Dharma Sawita, Dharma Wimala, Dharma Niskala, Dharma Sunya, and Dharma Putus, presents a textual discourse on kalepasan (liberation) as the essence of human spirituality and aesthetic experience in Old Javanese literature. This study aims to examine how KPD represents kalepasan as both ethical and aesthetic dimensions of spirituality, while also exploring the aesthetic experience of the kawi (poet) as an act of spiritual offering to the Creator. Employing a qualitative approach grounded in semiotics and hermeneutics, the research investigates the forms, functions, and meanings of kalepasan embedded in the language, symbols, and metaphors of the texts. The findings reveal that KPD articulates kalepasan not merely as a metaphysical doctrine but as an ethical–aesthetic practice rooted in humility, purification of the self, and the unification of the self (kawi), the cosmos, and the divine. The figure of the kawi-wiku, exemplified by Kamalanatha, embodies a paradoxical stance of self-negation and self-affirmation, thereby generating a profound aesthetic experience. Liberation in KPD is not achieved through ritual formalism alone, but through contemplative silence, the cessation of bayu, sabda, idep (energy, speech, thought), and the alignment with the niskala dimension. Silence (sunya, putus, nirbhana) thus emerges as both the key aesthetic category and the highest ethical ideal, signifying the peak of rasa and ineffable bliss. Accordingly, KPD may be regarded as a “temple of language,” where literature itself becomes a medium of inner yadnya (sacred offering) and a pathway to liberation. This study underscores the enduring significance of KPD not only as a philological and historical text, but also as a source of ethical and aesthetic spirituality relevant to contemporary reflections on human liberation.